2021
DOI: 10.1101/2021.08.20.457141
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Stable antibiotic resistance and rapid human adaptation in livestock-associated MRSA

Abstract: Mobile genetic elements (MGEs) often carry genes that benefit their bacterial hosts. In methicillin-resistant Staphylococcus aureus (MRSA), MGEs have been associated with antibiotic resistance, virulence, and host adaptation. Clonal-complex (CC) 398 is the dominant MRSA in European livestock, and a growing cause of human infections. To understand the risk posed by livestock-associated MRSA to human health, we have used a collection of 1,180 CC398 genomes, sampled from several livestock species and humans, with… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 86 publications
1
5
0
Order By: Relevance
“…Our results therefore suggest that the presence of S. aureus in this aquaculture environment is due to recent spillover from human populations. This is consistent with another study that showed the presence of a CC398 MSSA isolate from a gilthead seabream (35), which most likely originated from a human-associated lineage of CC398 (22,36,37). S. aureus have been recovered from municipal (65–68), hospital (69), and agricultural wastewaters/sewage (70), representing potential sources of human environmental contamination.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results therefore suggest that the presence of S. aureus in this aquaculture environment is due to recent spillover from human populations. This is consistent with another study that showed the presence of a CC398 MSSA isolate from a gilthead seabream (35), which most likely originated from a human-associated lineage of CC398 (22,36,37). S. aureus have been recovered from municipal (65–68), hospital (69), and agricultural wastewaters/sewage (70), representing potential sources of human environmental contamination.…”
Section: Discussionsupporting
confidence: 92%
“…Only one study by Salgueiro et al . (2020), performed genome sequencing and found CC398 methicillin-sensitive S. aureus (MSSA) (35), most likely human-associated (22,36,37). This study suggests that S. aureus is present in fish due to spillover from human populations but does not have the discrimination to test whether there is adaptation and persistence of S. aureus within fish populations or aquatic environments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the isolation rate of MRSA was low in our isolates, other isolates showed significant resistance to penicillins. Therefore, the prevalence of LA‐MRSA might be much higher in the future because of selective pressures (Matuszewska et al., 2022). Because LA‐MRSA might function as a reservoir for MRSA that can infect people (Fessler et al., 2011; Li et al., 2017b; Loncaric et al., 2013; Loncaric & Künzel, 2013), we suggest regular longitudinal surveillance of MRSA in livestock animals, especially pigs and chickens.…”
Section: Discussionmentioning
confidence: 99%
“…Using molecular typing with multi-locus sequence typing, MRSA clones found in pigs have been classified as clonal complex 398 (CC398) with sequence type 398 (ST398) [5]. In pigs, LA-MRSA is becoming increasingly resistant to several antibiotics commonly used in livestock, such as tetracycline, aminoglycoside, trimethoprim, and penicillin [6,7].…”
Section: Introductionmentioning
confidence: 99%